A Feasibility study on the local production of onion powder - Dela Fuente, Janelle S.; Madrinan, Sarah L.; Magno, Cheryl Omega M. (Diliman, Quezon City College of Engineering, 2002)
Onions are high value crop, second only to rice in its importance. The onion industry, however are currently plagued with problems. Onions are highly perishable and storage and transport of the products are only some of the problems the industry is facing. Excessive supply during harvest season and lack supply during off-season are also experienced. For this reason, the government launched projects to support post-harvest operations to help alleviate the situation and extend the shelf-life of harvest GOODS. At present, there are no local producers of onion powder. Onion powders are imported from different countries, mainly from United States. The market analysis aims to assess the current market conditions to determine whether the market conditions are favorable to the local production of onion powder. The analysis showed that there is sufficient demand for the product and it is projected that demand will continue to increase in the next five years. It is expected that urban households in the National Capital Region and the food processing industry will be the major consumers. The existence of several marketing media also makes it possible for the product to reach the target users. The technical analysis aims to determine if the means for production are available. The product will conform to the standards by the American Dehydrated Onions and Garlic Association since it will compete with foreign onion powder. It was determined that there is sufficient supply of onions of the yellow granex kind locally. Calcium stereate and flour can also be obtained locally. Production machinery and supplies area also available in the country and the company opted to obtain them locally. The facility will be located in Bulacan and designed to accommodate the projected demand. The total project cost is estimated to be PhP 30,500,000.00. The financial analysis aims to determine if the project is profitable. The MARR was set to be 20% as dictated by current industry practice. It was decided that equity financing will be used to avoid the high interest payments involved in debt financing. Four investors will contribute PhP 7,625,000 each to the owner's equity. The Net Present Value of the Project is PhP 119,063,701.07 which is much greater than zero. The Internal Rate of Return was computed to be 127.3% which is greater than the MARR of 20%. Other tests performed yielded favorable results. The sensitivity analysis also showed that the company will exceed the break-even values implying that it will be operating profitable. The payback is expected to be 5 years. The socio-profitability analysis aims to determine if the project is socially attractive. The analysis showed that the tangible and intangible benefits far outweigh the cost of the project. The venture was also compared to other investment alternatives and evaluated using the Net present Value. The organizational analysis justified the decision to use partnership as the form of organization. Four partners will share the ownership of the company. The jobs and job requirements were specified with the corresponding benefits and compensation. All the analyses performed yielded positive results. It was concluded that the project is feasible in all aspects.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Onion industry -- Philippines; Participatory monitoring and evaluation (Project management)